2022
DOI: 10.1007/s40520-021-02018-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving vaccination rates in older adults and at-risk groups: focus on pertussis

Abstract: Despite the implementation of effective paediatric vaccination programmes, pertussis remains a global health problem. Disease epidemiology has changed over time, shifting towards the adolescent and adult populations. In adults, the true burden of pertussis is greatly underestimated and pertussis vaccine coverage rates are suboptimal, including individuals with chronic conditions. Here, we report the outcomes of a virtual international scientific workshop to assess the evidence on the burden of pertussis in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
4
1
Order By: Relevance
“…Finally, the lowest vaccination coverage among the four vaccinations was observed for diphtheria-tetanus-pertussis. Even if the vaccination coverage in children against diphtheria-tetanus-pertussis is overall good [35], only one adult in three is protected against these infections [36], and this figure is probably lower in older adults [37]. Our study reported a significantly lower vaccination coverage of vaccination against diphtheriatetanus-pertussis when compared to US data [37].…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, the lowest vaccination coverage among the four vaccinations was observed for diphtheria-tetanus-pertussis. Even if the vaccination coverage in children against diphtheria-tetanus-pertussis is overall good [35], only one adult in three is protected against these infections [36], and this figure is probably lower in older adults [37]. Our study reported a significantly lower vaccination coverage of vaccination against diphtheriatetanus-pertussis when compared to US data [37].…”
Section: Discussioncontrasting
confidence: 58%
“…These variants were more toxic and infectious, with greater epidemic selection advantages [ 37 , 38 ]. With the decline in immunity over time and lack of booster vaccination, older people became more susceptible to B. pertussis [ 39 , 40 ]. In particular, the presentation of pertussis was generally less severe in adolescents and adults, which often caused medical professionals to miss out on their diagnosis, making them a potential source of transmission [ 41 ].…”
Section: Causes For Pertussis Resurgencementioning
confidence: 99%
“…1 , 8 The molecular pathogenesis of pertussis has been investigated in infants, for whom disease is severe. 22 Adolescents and adults less often present with the classic symptoms of pertussis, because they are usually milder than in children, 17 yet there are limited data available on the pathology of mild or typical pertussis in adults. 23 …”
Section: Etiology Transmission Pathogenesis and Presentation Of Pertu...mentioning
confidence: 99%
“…A previous publication examined methods to improve pertussis vaccination in at-risk groups including older adults. 17 The current publication, developed by an international panel of pertussis experts, builds on that article to provide up-to-date perspectives on the burden of pertussis in adults, identify current gaps in the evidence around adult Tdap vaccination, and lay out recommendations for future research directions.…”
Section: Introductionmentioning
confidence: 99%